Pengembangan LKPD berbasis Kolaboratif untuk Meningkatka Keterampilan Proses Sains dalam Pembelajaran IPA - Ulin Nuha; Yulia Chusnayani; Supeno; Diah Wahyuni; Rusdianto (Postgraduate, University of Mataram, 2023)
Science process skills need to be owned by students in learning science. With science process skills, it is easier for students to conduct research and solve life problems by implementing science learning outcomes. Nevertheless, science learning involving science process skills is still challenging for teachers. This study aims to produce collaborative-based worksheets on natural science learning materials in junior high schools. The type of research used is Research and Development with the Plomp development model, which consists of 3 stages: a preliminary study, a prototyping stage, and an assessment phase. The subjects used for product trials were class VIII students of SMP Negeri 2 Ajung Jember. The results showed that the validity of the collaborative-based worksheet obtained very valid criteria with a percentage value of 93.25%. Based on the practicality test, collaborative-based worksheets are included in the convenient category and are suitable for learning with a percentage of 96.45%. In the effectiveness test, a practical collaborative-based worksheet is proven to improve students' science process skills by acquiring the N-Gain of 0.6, which is included in the moderate criteria. Based on this study's results, we can state that the science process skills can be developed in students by conditioning science learning that optimizes collaborative activities.